Utilization of non-print resources and services of the Ateneo de Manila High School Instructional Technology Center by its faculty - Jordan, Heidi D. (2003)
The goal of teaching is the learning, processing and skill development that goes on in the students' heads. There are a variety of instructional methods for achieving this: it can be done by leading discussions, by developing special materials, by finding suitable materials developed by others, by developing thoughtful assignments, by explaining with guided note taking, and/or by having students explain concepts and material to each other.